2008
DOI: 10.1002/biof.5520330104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quercetin on oxidative nuclear and mitochondrial DNA damage

Abstract: Quercetin is a well-investigated antioxidant known to protect cells against oxidative nuclear DNA damage. There is no knowledge regarding its effect on oxidative mitochondrial DNA damage. In this study we investigated the effect of quercetin on oxidatively-injured DNA. Cell-free and cell studies were performed. Cell-free analyses carried out on plasmidic DNA showed that quercetin protects from all oxidative challenges used. Cellular studies were carried out on NCTC 2544 cells which were insulted with hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Keratinocytes NCTC 2544, incubated in DMEM, were exposed to 25, 50, 62.5 and 100 mg/mL of tendril aqueous extract for 24 h at 37°C. The membrane integrity was evaluated through the release of lactate dehydrogenase [28]. As shown in Figure 2, the keratinocytes were not damaged by the aqueous extract used in concentrations from 25 to 62.5 mg/mL.…”
mentioning
confidence: 98%
“…Keratinocytes NCTC 2544, incubated in DMEM, were exposed to 25, 50, 62.5 and 100 mg/mL of tendril aqueous extract for 24 h at 37°C. The membrane integrity was evaluated through the release of lactate dehydrogenase [28]. As shown in Figure 2, the keratinocytes were not damaged by the aqueous extract used in concentrations from 25 to 62.5 mg/mL.…”
mentioning
confidence: 98%
“…The QPCR assay had already been established with these primers in the authors' laboratory (33,34). The QPCR analyses of the two genomes showed that all three groups were not significantly different from one another, suggesting that oxidative damage in mtDNA ( Figure 3A) or in nDNA was not extensive ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin is a well-investigated antioxidant known as promising molecule for pharmacological studies. In a comprehensive research for DNA protection ability of quercetin, its supplementation indicated protection of nuclear DNA from oxidative damage and significant genoprotective activity on mitochondrial DNA (Potenza et al, 2008 ). In a different study, three polyphenolic compounds including luteolin, quercetin and rosmarinic acid, were investigated for their protective effects against oxidative DNA damage (Silva et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%